A Method for the Recovery of Gaps in General Analytic Signals. (7th September 2011) - Salomon, Benjamin G.; Ur, Hanoch
Abstract : We propose a generalized Papoulis-Gerchberg algorithm for the recovery of gaps in general analytic functions. The continuous-time algorithm is based on signal expansions in terms of the Chebyshev polynomials of the first kind, and the discrete-time implementation is based on a suitable nonuniform sampling scheme and the discrete cosine transform.